Sexual dysfunction among women in a Nigerian gynecological outpatients unit (2019)
Background: Sexual dysfunction is an important public‑health problem, which is often less reported or explored through opportunistic evaluation during medical consultations. Objective: This study was designed to determine the prevalence and patterns of female sexual dysfunction (FSD) including the sexual quality of life among female patients attending a gynecological outpatients unit in Southwest Nigeria. Materials and Methods: This is a cross‑sectional descriptive study of 146 consenting women who attended the gynecological outpatients’ clinic of the University College Hospital, Ibadan, Nigeria, during the study period. Participants were selected using multistage sampling technique. The survey instruments were previously validated questionnaires such as Sexual Function Questionnaire (SFQ28), Sexual Quality of Life‑Female Questionnaire (SQOL‑F), and the Family Adaptation, Partnership, Growth, Affection and Resolve (APGAR) score. The results were analyzed using Statistical Package for Social Sciences version 17 and P value was set at 5%. Results: The mean age was 33.8 ± 5.7 years. Most (85.6%) respondents had at least one form of sexual dysfunction. The commonest dysfunction was arousal‑sensation (62.4%) while the least was pain (3.4%). The mean SFQ28 and SQOL‑F scores were 58.0 ± 12.57 and 28.0 ± 11.94, respectively. There were no statistically significant differences in the SFQ28 and SQOL‑F scores across sociodemographic factors. Women classified as belonging to dysfunctional family on Family APGAR score similarly had poorer scores for sexual dysfunction (100%, P = 0.016). Conclusion: FSD is common among women attending gynecological outpatients clinic. Managing clinicians should be aware of this condition and proffer appropriate care in addition to the main presenting complaint.